2008
DOI: 10.4161/fly.6985
|View full text |Cite
|
Sign up to set email alerts
|

Biolistics for high-throughput transformation and RNA interference inDrosophila melanogaster

Abstract: With twelve Drosophila genomes now sequenced, there is a growing need to develop higher-throughput methods for identifying the functions of the many newly identified genes. Genetic transformation and RNA interference are two technologies that have been used extensively to facilitate gene-function studies in Drosophila melanogaster, to introduce genes or block the expression of endogenous genes, respectively. Both of these technologies typically require the delivery of nucleic acids into developing insect embry… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2009
2009
2017
2017

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 44 publications
0
7
0
Order By: Relevance
“…Previously, we have shown that injection or biolistic delivery of dsRNAs that target various genes essential to cell viability resulted in death of developing D. melanogaster embryos and larvae (Yuen et al, 2008). Ingested dsRNA has previously been shown to be lethal or produce deleterious effects in a limited number of insect species thus far (Baum et al, 2007;Mao et al, 2007;Zhou et al, 2008;Walshe et al, 2009), but not in drosophilids.…”
Section: Feeding Dsrnas Can Results In Species-specific Mortality Withmentioning
confidence: 99%
See 3 more Smart Citations
“…Previously, we have shown that injection or biolistic delivery of dsRNAs that target various genes essential to cell viability resulted in death of developing D. melanogaster embryos and larvae (Yuen et al, 2008). Ingested dsRNA has previously been shown to be lethal or produce deleterious effects in a limited number of insect species thus far (Baum et al, 2007;Mao et al, 2007;Zhou et al, 2008;Walshe et al, 2009), but not in drosophilids.…”
Section: Feeding Dsrnas Can Results In Species-specific Mortality Withmentioning
confidence: 99%
“…A transgenic strain of D. melanogaster carrying a ubiquitouslyexpressed b-glucuronidase gene (gus) under the control of the act5C promoter (Yuen et al, 2008) was used to test the efficacy of several different methods of dsRNA delivery, including feeding. By targeting a transgene that has no observable effect on the viability or fitness of the insects, RNAi could be induced without adversely affecting their growth or development.…”
Section: Rnai In D Melanogaster Using Different Dsrna Delivery Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…The technique has become a widely utilized system for the transformation of a wide range of organisms including insects (Yuen et al 2008 ), plants (Becker et al 2000 ;Fernando et al 2000 ;Fukuoka et al 1998 ;Klein et al 1988 ;Maenpaa et al 1999 ;RascoGaunt et al 1999 ;Tang et al 1999 ), animals such as Caenorhabditis elegans (Isik and Berezikov 2013 ), animal cells (Johnston 1990 ), algae (Mayfi eld and Kindle 1990 ), bacteria (Shark et al 1991 ), fungi (Bills et al 1995 ;Durand et al 1997 ;Fungaro et al 1995 ;St. Leger et al 1995 ), and intracellular organelles Larosa and Remacle 2013 ).…”
Section: Introductionmentioning
confidence: 99%